DEMOGRAPHIC STUDY OF MEDICOLEGAL AUTOPSY CASES CONDUCTED AT UTTARAKANNADA DISTRICT, KARNATAKA (Journal of Forensic Medicine & Toxicology, 2025)
casualties in future and to study the genuine crime rate in the area. Asphyxia causes most of the casualties, which lead to many deaths in the Uttar Kannada district. Objective: To set up a profile of deaths according to demographic details and to know most common cause of death, so that we can direct rigorous efforts to curb their incidence. Materials and Methods: We retrospectively studied the death cases brought for medicolegal autopsy, Karwar Institute of Medical Sciences, Karwar, Uttarakannada, Karnataka, India from the year 2016-2020. During this period, a total of 397 autopsy cases were conducted. Results: Of the total 397 cases, maximum numbers of autopsy cases [94 (23.68%)] were conducted in 2019.Maximum number of autopsy cases [43 (10.83%)] in month of May. Male cases predominated over the female cases, which were 324 (81.61%). The maximum numbers of cases [87 (21.91%)] were in the age group of 21–30 years. Asphyxia related deaths were more in number [179 (45.09%)] of the total cases. Shock and Hemorrhage accounted for 112 (28.21%) cases, Cardiac Failure accounted for 37(9.32%), followed by Respiratory failure [21 (5.96%)] cases. Conclusion: It is observed that the most common cause of death is Asphyxia, probably owing to higher frequency because of coastal area. The most common cause of death among asphyxia death was Drowning.
Keywords: Demographic; Retrospective; Medicolegal autopsy; Asphyxia; Drowning